2007
DOI: 10.1002/mds.21714
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of brain MRI and 18F‐FDG PET in the differential diagnosis of multiple system atrophy from Parkinson's disease

Abstract: To investigate the diagnostic value of brain magnetic resonance image (MRI) and (18)F-fluorodeoxyglucose positron emission tomography ((18)F-FDG PET) in the differentiation of multiple system atrophy (MSA) from Parkinson's disease (PD). Thirty-five patients with MSA (23 MSA-P and 12 MSA-C) and 17 patients with PD were included in this study. Overall correct diagnosis rates between clinical and imaging diagnosis among MSA-P, MSA-C, and PD patients were 80% for visual MRI analysis, 88.5% for visual (18)F-FDG PET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 31 publications
5
18
0
1
Order By: Relevance
“…On early phase images, a decrease or increase of regional uptake is shown in MSA-P, MSA-C, PSP, and DLB groups compared with the IPD group. These findings generally correspond with several previous studies that have identified characteristic DAT binding of neurodegenerative parkinsonism [32][33][34] and glucose metabolism patterns with IPD, MSA, PSP, and DLB [11,23,26,27], respectively. NA not applicable…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On early phase images, a decrease or increase of regional uptake is shown in MSA-P, MSA-C, PSP, and DLB groups compared with the IPD group. These findings generally correspond with several previous studies that have identified characteristic DAT binding of neurodegenerative parkinsonism [32][33][34] and glucose metabolism patterns with IPD, MSA, PSP, and DLB [11,23,26,27], respectively. NA not applicable…”
Section: Discussionsupporting
confidence: 92%
“…They classified these images as normal, MSA-P, MSA-C, PSP, or DLB, based on previous criteria of their glucose metabolism or brain perfusion, decreased regional uptake of the putamen, pons and cerebellum in MSA-P, decreased regional uptake of the cerebellum in MSA-C, decreased regional uptake of the caudate nucleus, the thalamus, midbrain and the cingulate gyrus in PSP, and decreased regional uptake of the occipital area, posterior cingulate cortex and temporo-parietal association area in DLB [11,22,[26][27][28]. The interobserver agreement and rate of correct classification were measured.…”
Section: Early Phase Imaging Analysesmentioning
confidence: 99%
“…Recently, Kwon et al, observed that MSA-P patients showed significant hypometabolism in the putamen [36]. In agreement with the results of this previous study, our results showed significantly decreased metabolic activity of the bilateral putamen in MSA-P compared with PD.…”
Section: Discussionsupporting
confidence: 95%
“…26,34 In the pons, there is the classic imaging finding of the "hot cross bun sign" (Fig 4). [35][36][37] With this atrophy, there may be a surrounding hyperintense rim seen on T2 images, which may appear before the hot cross bun sign, but it is unfortunately nonspecific, with atrophy being more important in distinguishing MSA from Parkinson disease. 36,38 T2* gradient-echo signal loss within the dorsolateral putamen reflective of increased iron deposition is highly specific for MSA, but not always present.…”
mentioning
confidence: 99%